Association of serum inflammatory markers in early-pregnancy with the risk for gestational diabetes mellitus: a prospective cohort in Shenzhen, China - Wang, Yijin; Ren, Qinqin; Yuan, Hui; Wang, Yang; Liu, Yao; Wei, Yuanhuan; Sun, Ruifang; Yang, Hongguang; Tian, Ping; Yang, Jianjun; Deng, Guifang (Frontiers in Endocrinology, 2025)
IntroductionThe systemic immune-inflammation index (SII) and systemic inflammation response index (SIRI) have recently been reported as novel inflammatory markers of diabetes. However, the associations of SII and SIRI with the risk of gestational diabetes mellitus (GDM) are unclear. In our study, we explored the association between the SII and SIRI in early pregnancy and the risk of GDM in pregnant women.MethodsA prospective cohort of 1,505 pregnant women were recruited at 6–13 weeks of gestation in 2019 and 2020 in Shenzhen, China. SII and SIRI were determined by calculating the composite inflammation indicators from routine blood test results at 6–13 weeks of gestation, and an oral glucose tolerance test was conducted at 24–28 weeks of gestation to diagnose GDM. Logistic regression was used to analyse the correlations between the incidence of GDM and SII and SIRI. Using a restriction cubic spline with baseline SII and SIRI as continuous variables, the dose–response associations between the incidence of GDM and SII and SIRI were explored.ResultsFollowing Ln-transformation of the SII and SIRI, multivariate models showed that Ln (SII) (odds ratio [OR] = 1.759; 95% confidence interval [CI]: 1.272–2.432) and Ln (SIRI) (OR = 1.556; 95% CI: 1.187–2.042) were positively associated with the risk of GDM in a dose-dependent manner. The OR for the highest quartile of SII compared with the lowest quartile for the risk of GDM was 2.080 (95% CI: 1.447–2.990), and the OR for the highest quartile of SIRI compared with the lowest quartile was 1.694 (95% CI: 1.170–2.452). The restricted cubic spline model confirmed a linear association between Ln (SII) and Ln (SIRI) with the risk of GDM (p-nonlinear > 0.05).DiscussionHigher SII and SIRI in early pregnancy are associated with an increased risk of GDM. As novel, valuable, and convenient indicators of inflammation, SII and SIRI could be used to a potential predictor for GDM in early pregnancy.